The Agricultural Productivity Gap and Self-Employment Bias in the Labor Income Share - Saumik Paul; Liam Thomas (Institute of Labor Economics (IZA), 2020)
We propose a theory-based adjustment to the labor income share to correct for the self-employment bias. Through a two-sector neoclassical framework with agriculture and non-agriculture, we derive the productivity-adjusted aggregate labor income share in terms of the agricultural productivity gap, and the labor income share in non-agriculture and value-added factor shares. We then construct a novel dataset on the labor income share at a sector level comprising of 53 countries. By applying the theory-based adjustment to our data, the average values for the aggregate and agricultural productivity-adjusted labor income share are 0.42 and 0.51, respectively. The gap between the productivity-adjusted and unadjusted figures are statistically significant only in agriculture, which can be attributed to the heavily underreported income from self-employed workers in agriculture. These findings appear robust at a more disaggregated level of non-agricultural sectors, as self-employment explains almost 98% of the variation in this gap.
Keywords: E24; E25; J30; 330; labor income share; cross-country data; income distribution; self-employment